POTRET BALIK DUNIA POLITIK ISLAM - Hasbi Sidik (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2013)
Islam is universal religion. An s Syahrur said that: from the end of nineteenth century until now, a popular slogan has been heard: 'Islam is the solution